Obesity and Hypogonadism-A Narrative Review Highlighting the Need for High-Quality Data in Adolescents - Tasnim Mushannen; Priscilla Cortez; Fatima Cody Stanford; Vibha Singhal (MDPI AG, 2019)
The prevalence of obesity continues to rise in adult and pediatric populations throughout the world. Obesity has a direct impact on all organ systems, including the reproductive system. This review summarizes current knowledge about the effects of obesity on the male reproductive system across age, highlighting the need for more data in children and adolescents. Male hypogonadism is commonly seen in patients with obesity and affects the onset, duration, and progression of puberty. Different pathophysiologic mechanisms include increased peripheral conversion of testosterone to estrone and increased inflammation due to increased fat, both of which lead to suppression of the hypothalamic-pituitary-gonadotropin (HPG) axis and delayed development of secondary sexual characteristics in adolescent males. Evaluation of the HPG axis in obesity includes a thorough history to exclude other causes of hypogonadism and syndromic associations. Evaluation should also include investigating the complications of low testosterone, including increased visceral fat, decreased bone density, cardiovascular disease risk, and impaired mood and cognition, among others. The mainstay of treatment is weight reduction, but medications such as testosterone and clomiphene citrate used in adults, remain scarcely used in adolescents. Male hypogonadism associated with obesity is common and providers who care for adolescents and young adults with obesity should be aware of its impact and management.